User experience with disinformation-countering tools: usability challenges and suggestions for improvement - Nault, Kimberley; Ruhi, Umar (Frontiers in Computer Science, 2023)
Digital media has facilitated information spread, and simultaneously opened a gateway for the distribution of disinformation. Websites and browser extensions have been put forth to mitigate its harm, however, there is a lack of research exploring their efficacy and user experiences. To address this gap, we conducted a usability evaluation of two websites and three browser extensions. Using a mixed method approach, data from a heuristic evaluation and a moderated, task-based usability evaluation are analyzed in triangulation with data collected via summative evaluations. Challenges are identified to stem from users' inability to understand results due to presentation of information, unclear terminology, or lack of explanations. As a solution, we recommend four design guidelines. First, is to establish credibility, second is to improve the general visual layout and design of the tools. Third, improve search capabilities, and lastly, heavy importance should be given to the depth and presentation of information.